Interactions of formaldehyde and its substituted derivatives with HCN: Structure, stability and interaction - Tri, Nguyen Ngoc; Minh Tam, Pham Thi; Hong Man, Nguyen Thi; Dai, Ho Quoc; Hung, Nguyen Phi; Trung, Nguyen Tien (Vietnam Journal of Chemistry, 2016)
Twelve stable structures of the interactions of HCN with RCHO (R = H, F, Cl, Br, NH2, CH3) are located on the potential energy surface at the MP2/aug-cc-pVDZ level. Interaction energies including both ZPE and BSSE corrections range from -5.80 to -21.07 kJ.mol-1. The result of SAPT analysis shows that the electrostatic component has mainly contributed to the stability of the complexes. It is remarkable that the most stable complex of HCHO∙∙∙HCN is P1-Hb which has not been reported in the literature. The red-shifting hydrogen bonds of the C-H∙∙∙O and N-H∙∙∙N types are observed in the P1-Hb, P1-CH3, P1-NH2 and P2-NH2 complexes. On the other hand, the C-H∙∙∙N(O) blue-shifting hydrogen bonds are observed in the rest of complexes. The contraction of C-H bond and the blue shift of its stretching vibrational frequency are inversely proportional with its polarity in the isolated monomer. Keywords. Hydrogen bond, interaction energy, RCHO, HCN, QTAIM, SAPT.